Against All Odds: An Archaeologist's Journey in Africa - Mekonnen, Degsew; Khaleel, Osman; Nyambiya, Humphrey; Maringa, Nompumelelo (Ex Novo: Journal of Archaeology, 2025)
This article addresses the myriad of challenges faced by young African archaeologists. Here, we reflect on our experiences as well as those of others by focusing on the pervasive problems of inadequate mentoring, lack of funding for important professional activities such as attending conferences and publishing, as well as limited access to opportunities. This study also examines the detrimental effects of these insurmountable barriers on professional development, networking opportunities, and dissemination of knowledge within the archaeological community. In addition, we explored other relevant obstacles faced by African archaeologists in the early stages of their careers, such as limited access to resources and navigating a competitive academic landscape. By highlighting these challenges, we aim to promote a deeper understanding of the systemic issues that hinder the development and sustainability of emerging talent in paleosciences and suggest possible strategies to mitigate these barriers.